Language evaluation by a speech therapist: Complementary assessment - Arroyo Carreras, Alicia; Díaz Martín, María; López Sáiz, Laura; Ortega Navarro, María (Pulso. Revista de educación, 2005)
This article is a continuation of the language Assessment article that was published in number 27 of Pulso magazine. In this one we have approached the complementary assessment, which includes language requirements (attention, imitation, memory, perception...), motor capacities, behaviour, reading and writing.These aspects are not components of the process of language, but they influence on it. We will analyze its concept and relation with the processes of language. Next we include an exemple of assessment record of language with evaluation items. Finally in this article we also show some tables with assessment language results. It will be useful for the speech therapist like an orientation about which language aspects he/she could center the future intervention on.